Screening of Microvascular Complications of Type-1 Diabetes Mellitus In A Tertiary Care Hospital (Journal of Fatima Jinnah Medical University, 2018)
Objectives: To study the biochemical status and screening of microvascular complications of type-1 diabetic patients.Study design and settings: It was a descriptive study carried out at Diabetic Clinic of PMRC Research Centre, FJMC, Lahore.Patients and Methods: Eight years case records of type-1 diabetic patients seen at the PMRC Research Centre FJMC Lahore from 1999-2006 were reviewed Out of 1265 diabetic patients sixty five were known type-1 diabetic. A 12 hours fasting blood sample was collected from each patient for serum total cholesterol , triglycerides , low-density lipoprotein cholesterol, high-density lipoprotein cholesterol, urea, creatinine, uric acid and glucose as well as glycosylated hemoglobin (HbA1c) by using standard methods performed at Biochemistry laboratory of the research centre. Body mass index (BMI) was calculated. HbA1c
Keywords: Type-1 diabetes mellitus, Complications, Coronary artery disease, nephropathy, neuropathy, renal, reproductive